Density and compressibility of the molten lunar picritic glasses: Implications for the roles of Ti and Fe in the structures of silicate melts. (15th January 2015) - Vander Kaaden, Kathleen E.; Agee, Carl B.; McCubbin, Francis M.
Abstract: The density and compressibility of four synthetic molten lunar picritic glasses was investigated from 0 to 10 GPa and 1748 to 2473 K. The picritic glasses were collected from the lunar surface during the Apollo missions, and they are hypothesized to have rapidly quenched as glass beads during pyroclastic fire fountain eruptions. The specific melt compositions investigated in the present study are the Apollo 15 green glass Type C (A15C, TiO2  = 0.26 wt%), the Apollo 14 yellow glass (A14Y, TiO2  = 4.58 wt%), the Apollo 17 orange glass 74220-type (A17O TiO2  = 9.12 wt%), and the Apollo 14 black glass (A14B, TiO2  = 16.40 wt%). These glasses are reported to represent primary unfractionated melts, making them a prime candidate for experimental studies into lunar basalt density and compressibility during partial melting of the lunar mantle. Sink–float experiments were conducted on the synthetic molten lunar glass compositions using a piston-cylinder apparatus ( P  < 2 GPa) and a Walker-style multi-anvil device ( P  > 2.5 GPa) in order to bracket the density of the melts. New sink–float data are reported for A15C, A14Y, and A17O, which are combined with previously published density and compressibility data on A15C, A17O, and A14B. Although the Ti-rich liquids are highly compressible at lower pressures, they become nearly incompressible at much higher pressures when compared to the molten low-Ti glasses. Consequently, the melts with the most TiO2 (A14B) are the least dense at higher pressures, a reversal of what is seen at lower pressures. This change in density and compressibility is attributed to changes in coordination of Ti and Fe in the silicate melt structure. As Ti 4+ abundances in the silicate melt increase, predominantly [IV] Ti 4+ and [IV] Fe 2+ change to [VI] Ti 4+ and [VI] Fe 2+ in the melt structure. All of the data from the present study were used to calculate a Birch–Murnaghan equation-of-state (BM-EOS) for each melt composition. The BM-EOS model for each composition was then combined with previously published estimates for the residual mantle source mineralogy and depth of origin for each of the glasses to assess the density of the partial melt with respect to its point of origin. This information was used to determine whether or not the melt would rise or sink with respect to its source region. We determined that all melt compositions, with the exception of the A17O melt, should have been able to rise to the crust-mantle boundary as a result of buoyancy forces alone, although different mechanisms are likely required for magma ascent through the lunar crust. For the rise of A17O, other modes of ascent through the lunar mantle are required to extract this melt composition from the mantle, and volatiles are not a plausible solution on the grounds of melt density alone.